2017
DOI: 10.15446/ing.investig.v37n1.57991
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodeoxygenation of furfuryl alcohol over Cu/MgAl and Cu/ZnAl catalysts derived from hydrotalcite-like precursors: A reaction for bio-oil upgrading

Abstract: The aqueous phase hydrodeoxygenation (HDO) of furfuryl alcohol over Cu/MgAl and Cu/ZnAl catalysts with different Mg/Al and Zn/ Al molar ratios, were investigated. Mg-Al and Zn-Al mixed oxides derived from hydrotalcites precursors were used as supports, which were impregnated with an aqueous solution of copper nitrate by incipient wetness impregnation. The HDO reaction was carried out in a typical batch reactor at 5 MPa of H 2 and 200 °C for 4 h. Among the catalysts studied, the Cu/MgAl-0.5 catalyst exhibited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…2-Cyclopentenone (CPEO) is generated via dehydration. Finally, the hydrogenation of CPEO generates CPO under a H 2 or D 2 atmosphere. The generated CPO in D 2 O shows an increased mass/charge ratio ( m / z ) than that in water, confirming the transfer of D atoms from D 2 O to intermediates and products during hydrogenation and rearrangement processes. This investigation confirms that water is a reactive solvent for the rearrangement process and a hydrogen source for the reaction.…”
Section: Resultsmentioning
confidence: 88%
“…2-Cyclopentenone (CPEO) is generated via dehydration. Finally, the hydrogenation of CPEO generates CPO under a H 2 or D 2 atmosphere. The generated CPO in D 2 O shows an increased mass/charge ratio ( m / z ) than that in water, confirming the transfer of D atoms from D 2 O to intermediates and products during hydrogenation and rearrangement processes. This investigation confirms that water is a reactive solvent for the rearrangement process and a hydrogen source for the reaction.…”
Section: Resultsmentioning
confidence: 88%
“…The protonated intermediate formation in aqueous phase and the subsequent transformations are catalysed by acidic sites. 48,49 However, the nickel catalysts supported on pure anatase titania have resulted in only the formation of CPO, whereas on mixed phase and rutile catalysts, additional deep hydrogenated products such as CPOL and THFOL are also formed. With the exception of the RTS catalyst, FOL is completely consumed in reaction over other mixed and rutile samples with a remarkable conversion of 100%.…”
Section: Temperature Programmed Reductionmentioning
confidence: 99%
“…These supports have been used in various types of reactions with biomass-derived model molecules, such as hydration reactions, aldol condensation, isomerization, among which HDO reactions have also been studied. Pino et al [136] used Cu catalysts supported on Mg and Al hydroxide hydrotalcites for the HDO reaction of furfuryl alcohol (200 • C and 50 bar). It was reported that the catalyst activity was dependent on the Mg 2+/ Al 3+ ratio, although most of the products obtained are oxygenated intermediates, not reaching complete deoxygenation of the furfuryl alcohol.…”
Section: Hdo Catalysts Supportsmentioning
confidence: 99%
“…Pino et al. [136] used Cu catalysts supported on Mg and Al hydroxide hydrotalcites for the HDO reaction of furfuryl alcohol (200°C and 50 bar). It was reported that the catalyst activity was dependent on the Mg 2+/ Al 3+ ratio, although most of the products obtained are oxygenated intermediates, not reaching complete deoxygenation of the furfuryl alcohol.…”
Section: Hdo Catalysts Supportsmentioning
confidence: 99%